2017
DOI: 10.5603/gp.a2017.0076
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable single incision sling Ajust — the effects of first operations controlled by pelvic floor sonography

Abstract: Objective: The aim of this study is to evaluate using PFS-TV the mid-term results of our first operative experience with implanting a single incision sling -Ajust™. Material and methods:One and the same surgeon has operated all the patients with symptoms of stress urinary incontinence. Ajust was the only performed procedure. Postoperative evaluation consisted of: a standardized interview and examination, a cough test and a PFS-TV for evaluation of urinary continence and tape location. PFS-TV was performed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…This study is one of only two evaluating the performance of Ajust® separately and one of few evaluating the performance of adjustable mini-slings as a group for periods longer than 2 years [20, 2527]. Therefore, the comparison of our results with those of other studies presents significant difficulties.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study is one of only two evaluating the performance of Ajust® separately and one of few evaluating the performance of adjustable mini-slings as a group for periods longer than 2 years [20, 2527]. Therefore, the comparison of our results with those of other studies presents significant difficulties.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the comparison of our results with those of other studies presents significant difficulties. Kluz et al [20] reported recently in a retrospective design on the outcomes of Ajust® 36–50 months after the operation. The post-operative evaluation was carried out through a combination of interview and examination and the observed cure rate of 51.6% is in agreement with our results based on the ICIQ-UI-SF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation